Vertebral hemangiomas in the thoracic spine of multiple sclerosis patients are connected with fewer demyelinating lesions at the same level. Possible impact on pathophysiology and clinical course. (2nd August 2016) - Anagnostouli, Maria; Katsavos, Serafeim; Kyrozis, Andreas; Gontika, Maria; Voumvourakis, Konstantinos I.; Kapaki, Elisabeth
Abstract : Objectives: Mechanisms of angiogenesis regulate multiple sclerosis (MS) lesions' evolution, displaying both neuroprotective and harmful effects. Factors traditionally considered as purely angiogenic, like vascular endothelial growth factor (VEGF), exert complex heterogenous actions on both neural and vascular malformation-derived tissues. Aim of this retrospective study was to examine, for the first time, potential associations between the presence of common vascular malformations, like vertebral hemangiomas (VHs), and several clinico-radiological MS parameters. Methods: 236 MS patients who were followed in our Outpatient Clinic were recruited in this study. Outcome measures concerned demographics, disease-derived variables, and MS-lesions' distribution in VHs – positive and negative patients. All data were collected retrospectively. Potential correlations were assessed with univariate statistical analyses ( p  = 0.05), followed by multivariate regression models, for purposes of confounder-effects elimination. Results: VH presence showed significant negative correlations with presence of MS lesions in the thoracic ( p  = 0.005 for thoracic VHs), but not the cervical cord. Trends towards negative associations of VH presence with subtentorial MS lesions and positive family history for MS were also observed. Discussion: Our observations suggest that VH presence may reduce the risk of thoracic demyelinating lesions in MS patients. They could be explained as part of a multifaceted angiogenic process, concomitantly enhancing neural repair and abnormal hemangioma vascularization.